Relationship of Latvian communist party and Latvian SSR KGB (1954–1991) - Jansons , Ritvars (Genocidas ir rezistencija, 2006)
The Latvian Communist Party (LKP) and the Latvian KGB were the most important institutions controlling Latvian society throughout the communist occupation. Working together, the LKP and the KGB of the Latvian SSR carried out political repression of the Latvian population, which were only discontinued in the second half of 1990s. The analysis of the relationship between LKP and KGB is important as this will help to shed light on how the existing regime in Latvia carried out the repressions and controlled society. The available information suggests that in 1960–1980 the KGB of the Latvian SSR acted not only as a perpetrator but also as an initiator, promoting the improvement of the system of society’s control established in the Latvian SSR. In my opinion, full and accurate lustration is possible only subject to individual responsibility of each institution and persons, both for the repression against the population and for the control of society for the benefit of the communist regimes.
Keywords: Latvia; KGB; communist party; repressions; lustration